Removal of iron and manganese from acidic aqueous solution by pyrite and pyrite-calcium sulfite - Xu Zhang; Yajing Wang; Gesang Nima; Ziqian Wang; Caifeng Huang (Scientific Reports)
Abstract Pyrite and calcium sulfite were used to remove iron and manganese from an acidic aqueous solution. The concentration of Fe was decreased to be smaller than 0.05 g/L in 60 min when pyrite and air were added into the acidic aqueous solution, but the concentration of Mn in the solution remained unchanged. After the process of iron removal, calcium sulfite and air were used to remove manganese ions from the solution, and the efficiency of manganese ion removal was larger than 75% in 240 min (with less than 0.05 g/L Fe and 0.5 g/L Mn in the solution). Meanwhile, experiments were conducted to simultaneously remove iron and manganese from artificially simulated acidic leaching solution of laterite nickel ore. When the proposed method was used to purify the leaching solution of laterite nickel ore, Fe3+ and Mn2+ ions were effectively removed from the acidic solution, and the recovery efficiency of nickel and cobalt was greater than 98%.